Measurements of the expansion velocities of ionized-gas superbubbles in nearby galaxies based on integral field spectroscopy data - Smirnov-Pinchukov, Grigorii; Egorov, Oleg (Astrophysical bulletin, 2021)
The study of dynamic properties of bubbles in the interstellar medium is important for understanding the feedback mechanisms from star-formation processes in galaxies. The ongoing integral field spectroscopy of nearby star-forming galaxies reveals many expanding bubbles and superbubbles identified by the local increase in gas velocity dispersion. The limited angular resolution often prevents bona fide measures of the expansion velocities in galaxies outside the Local Group, even despite sufficient spectroscopic resolution. We present a method that makes it possible to measure the expansion velocity of bubbles surrounding massive stars and clusters based on the data about local variations in gas velocity dispersion. We adapt the method for the Fabry-Perot interferometers used with the 6-m telescope of the Special Astrophysical Observatory of the Russian Academy of Sciences, as well as for any integral field spectrograph with a Gaussian line spread function. We apply the method described to analyze the kinematics of ionized superbubbles gas and the only known supernova remnant in the IC 1613 galaxy. The estimate of the kinematic age of the supernova remnant (on the order of 3100 years) agrees well with the previously obtained independent estimate based on X-ray data.
Gesehen am 15.02.2022